Transportation of cuttings by drilling mud in horizontal wells. Part 2. Numerical results of drilling at optimal rheological properties of mud - Sergey N. Kharlamov; Mehran Janghorbani; Artem G. Chernov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
The relevance. Ensuring technological equipment operation efficiency when drilling wells with an arbitrary orientation of their wellbores. In particular, the search for productive hydrocarbon reservoirs requires drilling deeper wells with extended horizontal sections, for which the removal of the cuttings bed is the key problem of modern drilling. The aim. Study the features and establish the patterns of cuttings movement through the annulus eccentric space formed by a drill string and well walls under various modes (in-situ) and drilling conditions within the framework of modern mathematical models of hydrodynamics, numerical algorithms and approaches implemented in ANSYS CFD. Optimize the parameters that determine drilling, such as an inclination angle, mass-average velocity and morphology of the inlet rheologically complex viscous flow to form the maximum allowable drilling velocity for various combinations of mud effective viscosity and mixture flow rate. Give practical recommendations for engineers to reduce time, costs and material resources for maintenance and optimization of well cleaning. The object.  A well with an eccentric core and an extended horizontal section operating in modes and conditions close to real drilling. The methods. Complex of physical and mathematical analysis and numerical modeling of hydrodynamics and mass transfer in homogeneous and heterogeneous continuous media. The media were widely tested on the class of internal rheological complex flows, the verification of which was carried out under appropriate conditions, performed by other authors when solving problems of drilling and cleaning wells. The results. The paper presents the results of a numerical study of hydrodynamics of a dispersed flow of a rheological complex viscous mixture of a drilling fluid with the properties of a Herschel–Bulkley type fluid and sand particles in wells with an arbitrary generatrix of its wellbore in an eccentric space. The results are required to clarify the features that accompany direct-flow and swirling flow (the moving wall method), identify the patterns in such modes, accounting for which allows for effective cleaning of the annulus. The calculations were performed within the framework of modern mathematical models of the RANS-method and the Euler–Lagrangian approach to describing the motion of heterogeneous media, implemented in the ANSYS CFD software and efficient numerical algorithms for determining intra- and interfacial processes of mass and momentum transfer in mixtures. The authors have determined that when drilling a vertical section, the most effective parameter in terms of cleaning control is the effective viscosity of the mud; the most problematic configurations for cleaning are wells with sloping sections at angles close to the vertical. When drilling a horizontal section, the eccentricity of the drill string creates “the dead” zone of flow and complicates cleaning. This zone should be removed by creating swirling flow conditions through relatively weak rotation of a drill string (30–60 rpm). When drilling inclined sections, it is necessary to reduce a solution viscosity (preferably to the level of fresh water) and increase the flow rate (in this case, to 2 m/s or higher). When drilling a horizontal section, a mud with a viscosity close to fresh water is recommended at flow rates of about 2 m/s (or 640 gpm) at the well inlet and a maximum drilling velocity of 9 m/h.